Frequency and chronological distribution of linear enamel hypoplasia (LEH) in the Late Neolithic and Early Bronze Age population from Żerniki Górne (Poland) – preliminary report - Tomczyk, Jacek; Tomczyk-Gruca, Maria; Zalewska, Marta (Anthropological Review, 2012)
Linear enamel hypoplasia (LEH) is treated as a nonspecific indicator of stress, but even so, many authors consider it the most reliable tool stress in anthropological research. Its analysis allows the reconstruction of health related to the socio-economic status of the group. This study documents and interprets patterns of LEH in Żerniki Górne (Poland), a settlement which was functional in the Late Neolithic and the Early Bronze Age. We examined two successive cultures: the Corded Ware Culture (CWC; 3200–2300BC) and the Trzciniec Culture (TC; 1500–1300BC). In total, there were 1486 permanent teeth (124 adult individuals). The frequency of LEH in the examined cultures shows a small rising trend. In these series from Żernik Górne, males showed a higher occurrence of LEH (16.5%) than females (13.4%). The earliest LEH appeared at similar ages at about 2.0/2.2 years and the last LEH occurred at about 4.2 years of age in both cultures. However, it is worth noting that periods associated with physiological stress were more common but not very long (four months on average) in the CWC. Longer stress periods (nine months on average) were associated with the TC.